Effects of cerium on the antioxidant defence system in the petals and the contents of pigments in the calyces of Rosa chinensis Jacq. cut flower. Issue 6 (2nd November 2017) - Wang, Qiaojian; Mu, Jinyan; Shan, Changjuan; Wang, Weiyan; Fu, Songling
ABSTRACT: To study the role of cerium (Ce) in regulating the vase life of Rosa chinensis Jacq. cut flowers, the effects of cerium nitrate (Ce(NO3 )3 ) on the activities of antioxidant enzymes, the contents of malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) in the petals, and the contents of chlorophyll a, chlorophyll b and carotenoids in the calyces were investigated. The results showed that Ce(NO3 )3 evidently enhanced the activities of peroxidase (POD), catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), glutathione S-transferase (GST) and glutathione peroxidase (GPX), and evidently decreased the contents of MDA and H2 O2 in the petals, compared with the control. Moreover, Ce(NO3 )3 evidently increased the contents of chlorophyll a, chlorophyll b and carotenoids in the calyces. The results also showed that Ce(NO3 )3 evidently increased the numbers of open flowers and decreased the numbers of wilted flowers. Our results suggest that Ce(NO3 )3 extended the vase life of R. chinensis Jacq. cut flower by improving the antioxidant defence system in the petals and the contents of pigments in the calyces.